The recognition and removal of cellular poly(ADP‐ribose) signals. (18th June 2013) - Barkauskaite, Eva; Jankevicius, Gytis; Ladurner, Andreas G.; Ahel, Ivan; Timinszky, Gyula
<x xml:space="preserve">Abstract</x> Poly(ADP‐ribosyl)ation is involved in the regulation of a variety of cellular pathways, including, but not limited to, transcription, chromatin, DNA damage and other stress signalling. Similar to other tightly regulated post‐translational modifications, poly(ADP‐ribosyl)ation employs 'writers', 'readers' and 'erasers' to confer regulatory functions. The generation of poly(ADP‐ribose) is catalyzed by poly(ADP‐ribose) polymerase enzymes, which use NAD+ as a cofactor to sequentially transfer ADP‐ribose units generating long polymers, which, in turn, can affect protein function or serve as a recruitment platform for additional factors. Historically, research has focused on poly(ADP‐ribose) generation pathways, with knowledge about PAR recognition and degradation lagging behind. Over recent years, several discoveries have significantly furthered our understanding of poly(ADP‐ribose) recognition and, even more so, of poly(ADP‐ribose) degradation. In this review, we summarize current knowledge about the protein modules recognizing poly(ADP‐ribose) and discuss the newest developments on the complete reversibility of poly(ADP‐ribosyl)ation.